Characterization of whey protein-carboxymethylated chitosan composite films with and without transglutaminase treatment. (20th November 2016) - Jiang, Shu-juan; Zhang, Xuan; Ma, Ying; Tuo, Yanfeng; Qian, Fang; Fu, Wenjia; Mu, Guangqing
Highlights: WPC-CMC composite film attained markedly improved mechanical resistance and solubility. TGase favored water barrier capability and mechanical resistance of composite films. Abstract: Edible composite packaging has the advantage of complementary functional properties over its each bio-components. However, reports on whey protein concentrates (WPC)-carboxymethylated chitosan (CMC) composite films have not yet been released. To investigate the preparation of WPC-CMC composite films and its functional properties, four types of WPC-CMC composite films were prepared with and without Transglutaminase (TGase) treatment by mixing WPC aqueous solutions (10%, w/v) with CMC aqueous solutions (3%, w/v) at WPC to CMC volume ratios of (100:0), (75:25), (50:50), and (25:75). SDS-PAGE confirmed that TGase catalyzed crosslinking of whey protein. Results revealed that CMC incorporation conferred a smooth and even surface microstructure on the films and markedly improved the transparency, water barrier properties, mechanical properties and solubility of the composite film. Furthermore, TGase resulted in an improvement in the water vapor barrier properties and mechanical properties of WPC-CMC (75:25 and 50:50, v/v) composite films, and there was no impairment of thermal stability of composite films. Therefore, TGase successfully facilitated the formation of WPC-CMC composite films with some improved functional properties. This offers potential applications as an alternative approach to the preparation of edible packaging films.